Resource-Based Contingencies of When Team–Member Exchange Helps Member Performance in Teams - Farh, Crystal I. C.; Lanaj, Klodiana; Ilies, Remus (Academy of Management Journal, 2017)
We integrate social exchange theory with social capital theory to present a resource-based contingency model of when team–member exchange (TMX) helps individual performance in teams. We argue that strong TMX produces obligations to utilize resources (e.g., task information) provided by one’s teammates, and these obligations enhance performance when (a) teammates provide resources of high quality or (b) the quality of resources available from individuals outside of the TMX relationship (i.e., the leader) are low, purportedly because TMX-based obligations protect individuals from over-utilizing low-quality resources from the leader. We tested our model in two studies. In Study 1, multisource team data revealed that TMX enhanced member performance when teammates possessed attributes associated with high-quality resources (i.e., high cognitive ability) or when the leader did not. In Study 2, we replicated these findings in a scenario experiment, showing that TMX impacted performance under different resource conditions via felt obligation to utilize teammates’ resources. Our findings advance the literature by delineating the teammate- and leader-resource conditions under which TMX benefits member performance, as well as demonstrating that felt obligation to utilize teammates’ resources is an important mechanism underlying these effects. Theoretical and practical implications are discussed.